الاختصاص التكميلي للمحكمة الجنائية الدولية - شهيناز زعلاني; علي بوضياف (My University, 2025)
Abstract: This study addressed the subject of the complementarity jurisdiction of the International Criminal Court (ICC) as one of the fundamental pillars of the Rome Statute and a key mechanism for ensuring the realization of international criminal justice without infringing upon the sovereignty of states. The first chapter examined the historical background of the Court, the motivations behind its establishment, its institutional structure, and its various jurisdictions namely subject-matter, personal, territorial, and temporal. The second chapter was dedicated to analyzing the principle of complementarity, focusing on its definition, evolution, the conditions for its activation (namely, unwillingness and inability), as well as the legal and political challenges associated with its application. The study concluded that the ICC represents a significant advancement in the international justice system. However, its effectiveness remains constrained by several obstacles, most notably: the difficulty in proving a state's unwillingness or inability to prosecute, the issue of official immunities, the intervention of the UN Security Council, and the lack of international cooperation in certain contexts. The study further highlighted the importance of strengthening national judicial systems and enhancing mechanisms for the effective implementation of the complementarity principle. Several recommendations were proposed to ensure a more effective application of complementarity and to achieve the necessary balance between respecting national sovereignty and combating impunity. ..................... الملخص تناولت هذه الدراسة موضوع الاختصاص التكميلي للمحكمة الجنائية الدولية باعتباره أحد الركائز الجوهرية في نظام روما الأساسي، وآلية أساسية لضمان تحقيق العدالة الجنائية الدولية دون المساس بسيادة الدول. تم التطرق في الفصل الأول إلى النشأة التاريخية للمحكمة، دوافع إنشائها، تركيبتها المؤسسية، واختصاصاتها الموضوعي الشخصي المكاني والزماني). بينما خُصص الفصل الثاني لتحليل مبدأ الاختصاص التكميلي، من حيث تعريفه، تطوره، شروط تفعيله عدم القدرة ، وعدم الرغبة، والإشكالات القانونية والسياسية التي يثيرها تطبيقه. خلصت الدراسة إلى أن المحكمة الجنائية الدولية تمثل نقلة نوعية في نظام العدالة الدولية، غير أن فعاليتها لا تزال مقيدة بعوائق متعددة أهمها : صعوبة إثبات عدم رغبة أو عدم قدرة الدول على الملاحقة القضائية، الحصانات الرسمية، تدخل مجلس الأمن، وغياب التعاون الدولي في بعض السياقات. كما أبرزت الدراسة أهمية تعزيز قدرات الأنظمة القضائية الوطنية وتطوير أدوات تفعيل مبدأ التكامل. وقد تم تقديم عدد من التوصيات لضمان تطبيق أكثر فعالية لمبدأ الاختصاص التكميلي، وتحقيق التوازن المطلوب بين احترام السيادة الوطنية ومكافحة الإفلات من العقاب. ............................. Résumé Cette étude aborde la compétence complémentaire de la Cour pénale internationale (CPI), l'un des piliers du Statut de Rome et un mécanisme fondamental pour garantir la mise en œuvre de la justice pénale internationale sans compromettre la souveraineté des États. Le premier chapitre aborde les origines historiques de la Cour, les motivations de sa création, sa structure institutionnelle et ses compétences matérielles (spatiales, temporelles et personnelles). Le deuxième chapitre analyse le principe de compétence complémentaire, notamment sa définition, son évolution, ses conditions de fonctionnement (incapacité, réticence) et les défis juridiques et politiques posés par son application. L'étude conclut que la CPI représente une évolution qualitative du système de justice internationale. Cependant, son efficacité reste limitée par plusieurs obstacles, notamment : la difficulté de prouver la réticence ou l'incapacité des États à poursuivre, les immunités formelles, l'intervention du Conseil de sécurité et le manque de coopération internationale dans certains contextes. L'étude souligne également l'importance de renforcer les capacités des systèmes judiciaires nationaux et de développer des outils pour mettre en œuvre le principe de complémentarité. Plusieurs recommandations sont présentées pour assurer une application plus efficace du principe de compétence complémentaire et pour atteindre l’équilibre requis entre le respect de la souveraineté nationale et la lutte contre l’impunité.
Keywords: Keywords: Complementarity Principle - International Criminal Court - Rome Statute - Complementary Jurisdiction.; الكلمات المفتاحية : مبدأ التكامل - المحكمة الجنائية الدولية - نظام روما الأساسي - الاختصاص التكميلي.; Mots-clés : Principe de complémentarité - Cour pénale internationale - Statut de Rome - Compétence complémentaire.